This is my father [videorecording (Blu-Ray)] - Quinn, Paul, 1960-2015; Quinn, Aidan; Caan, James; Rea, Stephen; Cusack, John, 1966- (Sony Pictures Classics, 2025)
A drama about a scandalous romance and its impact on the future generations of one family. After he discovers a fifty-year-old photograph of his mother and a mysterious young man, burned-out Chicago schoolteacher Kieran Johnson travels to Ireland in search of the answers she can no longer give him. Arriving in the village where she was born, her rooms at a bed and breakfast run by a fortuneteller who remembers Kieran's mother. As he recalls the details of his mother's star-crossed love affair, Kieran, for the first time in his life, is able to come to terms with who he is and where he came from.